Between ‘NET’ and ‘CoGNET’: A biphasic Neuroendocrine-Gangliocytic tumor of the pancreas - Binny Khandakar; Moreen Ng; Laura Baum; Marie E. Robert (Human Pathology Reports)
While neuroendocrine tumors of the pancreas are increasing in incidence, neural derived tumors are only rarely found in this organ. Paragangliomas, neuronal and nerve sheath tumors of the pancreas are limited to small series or case reports. The newly named composite gangliocytoma/neuroma and neuroendocrine tumor (CoGNET), formerly gangliocytic paraganglioma, occurs almost exclusively in the second part of the duodenum and periampullary region but has been reported in the pancreas. At the time of this writing four pancreatic CoGNETs have been reported in the pancreatic head, ranging in size from 2.2 to 5.3 cm; three in females, with a mean age of 63 years (range, 50–74 years). Herein, we report the clinico-pathologic findings of a 58-year-old male presenting with a low-grade neuroendocrine tumor showing focal gangliocytic differentiation within the head of pancreas that does not fit precisely into existing tumor classifications, having some but not all elements of CoGNET. The morphology and immunohistochemical profile of the tumor are presented in the context of the differential diagnosis and prior literature.